Implementasi Model Pembelajaran Discovery Learning guna Meningkatkan Minat Belajar pada Pelajaran Penjasorkes Peserta didik Kelas XI IPA 1 di MAN 2 Kota Padang - Akhri Meinhardi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The problem in this study is the low student achievement which is thought to be due to the lack of student interest in participating in learning activities. One of the efforts to increase students' interest in learning is to utilize the Discovery Learning learning model, because the learning model is Discovery Learning. has the appropriate characteristics to solve problems that occur so that the learning process becomes more effective, besides the Discovery Learning learning model is in accordance with the curriculum applied at MAN 2 PADANG. This type of research is classroom action research. The results of the implementation of the Discovery Learning learning model in the first cycle reached 91.67%, while in the second cycle the implementation of the Discovery Learning learning model was able to reach 100%. So it can be concluded that the implementation of the Discovery Learning learning model has been carried out optimally in cycle II.a Furthermore, the results of data on student interest in learning in cycle I show that student interest in learning is 72.19%, while data on student interest in learning in cycle II is 80.12%, so it can be concluded that the interest of the students increased in accordance with the predetermined success indicator limit, which was 80%, and was achieved after the second cycle took place. That is, it can be concluded that the implementation of the Discovery Learning learning model can increase the learning interest of the students of class XI IPA 1 MAN 2 Padang City. This is evidenced by the increasing percentage of students' interest in learning to achieve predetermined success indicators..